Confucian philosophy for contemporary education - Tan, Charlene (London ; New York : Routledge, 2021)
Most people would not associate Confucian philosophy with contemporary education. After all, the former is an ancient Chinese tradition, and the latter is a modern phenomenon. But this book shows otherwise, by explaining how millennia-old Confucian ideas and practices can inform, inspire and improve school administration, teaching and learning today. Drawing upon major Confucian texts such as the Analects and Mencius , as well as influential thinkers such as Confucius, Zhu Xi and Empress Xu, the various chapters address current educational issues and challenges such as the following: What roles do schools play in fighting the coronavirus pandemic? How can humanity resolve the climate emergency? What (more) should school leaders do to promote education for girls? Is there more to lifelong learning than just skills upgrading? What is missing in the existing frameworks on 21st century competencies? What new initiatives are needed to champion sustainable development? Confucian Philosophy for Contemporary Education answers the above questions and more by presenting a Confucian model of education. The author proposes a Confucian school where Dao - a shared vision of human excellence - is realised through a mindful, learning-centred, action-oriented and ultimately humanising form of education. This book is a useful resource for academic researchers, educators, students and general readers on Confucian philosophy and its continual relevance for present-day education.
OCLC-licensed vendor bibliographic record.
Keywords: Confucianism and education; EDUCATION / Philosophy & Social Aspects